2017
DOI: 10.18632/oncotarget.16284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long non-coding RNAs that stimulate cell survival in bladder cancer

Abstract: For many years, research on the biology underlying bladder cancer focused on protein-coding genes which cover only about 3% of the human genome. Recently, it was discovered that a large part of the human genome is actively transcribed as long non-coding RNAs (lncRNAs). LncRNAs are master regulators of gene expression and several lncRNAs were shown to play a role in bladder cancer development and progression. Here, we analyzed lncRNA expression in muscle-invasive bladder cancer (MIBC) using the MiTranscriptome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Previously, lncRNAs have been observed to serve as tumor suppressors or oncogenes because their dysregulation can promote or suppress the proliferation, migration, and invasion of BC cells [25][26][27]. In this study, because of the upregulation of LINC00707 in BC, we wondered that LINC00707 may act as a tumor promoter in BC.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, lncRNAs have been observed to serve as tumor suppressors or oncogenes because their dysregulation can promote or suppress the proliferation, migration, and invasion of BC cells [25][26][27]. In this study, because of the upregulation of LINC00707 in BC, we wondered that LINC00707 may act as a tumor promoter in BC.…”
Section: Discussionmentioning
confidence: 92%
“…No additional studies were identified by a manual search of the references of the original studies. Finally, the remaining 37 articles were eligible for the systematic review (Wang et al, 2006 ; He et al, 2013 , 2016a , b ; Fan et al, 2014 ; Li et al, 2014 , 2017 ; Srivastava et al, 2014 ; Yan et al, 2014 ; Chen et al, 2015 , 2017 ; Eissa et al, 2015a , b ; Milowich et al, 2015 ; Zhao F. J. et al, 2015 ; Zhao X. L. et al, 2015 ; Duan et al, 2016 ; Iliev et al, 2016 ; Zhan et al, 2016a , b , 2017a , b ; Zhang et al, 2016 , 2017 ; Cao et al, 2017 ; Cui et al, 2017 ; Dudek et al, 2017 ; Du et al, 2017 ; Hu Y. Y. et al, 2017 ; Liao et al, 2017 ; Lin et al, 2017 ; Tolkach et al, 2017 ; Wu et al, 2017 ; Xiong et al, 2017 ; Yang et al, 2017 ; Ye et al, 2017 ; Zhuang et al, 2017 ), including 26 studies for clinicopathological parameters, 19 studies for prognosis, and 7 studies for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, an observed HR > 1 implied that the patients with increased lncRNAs expression had a worse survival. Increased expressions of MALAT1 (Fan et al, 2014 ; Li et al, 2017 ), ASAP1-IT1 (Yang et al, 2017 ), SPRY4-IT1 (Zhao X. L. et al, 2015 ), TUG1 (Iliev et al, 2016 ), lncRNA-n336928 (Chen et al, 2015 ), GHET1 (Li et al, 2014 ), linc-UBC1 (He et al, 2013 ), YRNA5 (Tolkach et al, 2017 ), XIST (Hu Y. Y. et al, 2017 ), PVT1 (Cui et al, 2017 ), and SNHG16 (Cao et al, 2017 ) were significantly correlated with poor prognosis in OS, along with decreased expressions of CAT1297 (Dudek et al, 2017 ), lncRNA-LET, YRNA1 (Tolkach et al, 2017 ), YRNA3 (Tolkach et al, 2017 ), YRNA4 (Tolkach et al, 2017 ), and NBAT1 (Du et al, 2017 ). It was worth noting that the most significant association was observed between increased expressions of SPRY4-IT1 and poor OS (HR = 3.716; 95% CI: 2.084–6.719; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…In previous researches, many different lncRNAs had been identified in bladder cancer, such as FOXD2-AS1, CAT266, CAT1297, CAT1647, LINC00857 and BANCR. [18][19][20][21] One of the main ways for lncRNAs to participate in tumor development is to act as an endogenous competitive RNA of microRNAs (miRNAs) and indirectly regulates gene expression post-transcriptionally. 5 LINC00963 has been found to be an oncogene in several human malignant tumors, including breast cancer, hepatocellular carcinoma, esophageal squamous cell carcinoma, etc.…”
Section: Discussionmentioning
confidence: 99%